(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this novel, it is hardly a coincidence that Daniel Martin is reproached for his chauvinism by Jenny McNeill in much of the same way as is Miles Green by Erato. The theme of the complicity of the author or the narrator in the creation and propagation of certain male-biased stereotypes of women had already been foreshadowed in FLW, but it is in these three books that it comes out most clearly. This is because of the fact that it is these three books who concentrate on the act of writing fiction itself. It is shown that while fiction can help to deconstruct certain meta-narratives, the author himself (the pronoun being deliberately masculine here) is at times propagating the very stereotypes he’s trying to deconstruct. Finally, in Daniel Martin, Fowles illustrates the literal and metaphorical quest and the self-discovery of his character Daniel Martin (Dan), who struggles to shape his identity and his art, to acquire a sense of unity and to see life and himself totally. In this sense, in the novel, the multiplicity of the fragmented and discontinuous narrators, characters, settings and events, the shift of time and places, simultaneous forward and backward movements, reflect the distinctive characteristics of the postmodern novel. Consequently, in Fowles’s Daniel Martin, the fragments of Dan’s life are portrayed within the fragmented and discontinuous texts in which Dan attempts to capture reality, to realize the connection of his past with his present and to gain whole sight. In this postmodern context, the protagonist’s attempts to discover his identity, to broaden his mind and enlarge his vision through his quest, like the efforts of the protagonist in a Victorian Bildungsroman, contribute to the unique and distinctive structure of the novel, thus at the end the protagonist achieves realizing his unexplored identity through his quest.